Implementation of a Bowel Management Program in Critical Care. Issue 4 (July 2015) - Pittman, Joyce; Beeson, Terrie; Carter, Brandt; Terry, Collin
Abstract : PURPOSE: The purpose of this study was to examine the effectiveness of a unit-based, educational program on implementation of a sustainable bowel management program in a critical care setting. SUBJECTS AND SETTING: Two hundred thirty nurses in 6 critical care units within a 750-bed level I trauma hospital and 400-bed university academic teaching hospital participated in the study. METHODS: Data collection and analysis were guided by a quasi-experimental pre-/postdesign. An evidence-based, interactive Web-based education program was developed. The education program consisted of 3 components: (1) knowledge acquisition (Web-based education module), (2) skill acquisition (unit-based skill session performance and competency), and (3) mastery experiences (self-efficacy). Data collected included pre- and posteducation module test scores, skill-acquisition competency, and self-efficacy scores. RESULTS: The Web-based education module pre- and posttest scores for 225 participants showed significant ( P < .001) improvement in knowledge scores. All participants (100%) completed the skill acquisition sessions successfully during the unit-based performance session. Nurses' self-efficacy scores significantly improved ( P < .001) over the course of this study period. Eighty-six percent (n = 125) of critical care nurses reported enhanced collaboration with the WOC nurses and clinical nurse specialists. CONCLUSION: Study findings support the use of a structured, evidence-based educational program incorporating a multimethod approach to implement practice change for critical care. Abstract : The CE test for this article is available online only at the journal website, jwocnonline.com, and the test can be taken online at NursingCenter.com/CE/JWOCN.